2022
DOI: 10.1007/s13555-022-00701-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Hidradenitis Suppurativa Severity: Is It Useful for Clinical Practice?

Abstract: Introduction: Hidradenitis suppurativa (HS) is considered to be the most burdensome dermatosis, with a well-documented negative influence on quality of life (QoL). The patient's perception of the disorder, assessed as the selfreported severity, has been used in other dermatoses but not in HS. The aim of this study was to evaluate the usefulness of self-reported HS severity in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The significant impact of HS on patients’ quality of life, as reflected in our analysis, aligns with previous research underscoring the considerable burden of this condition [ 28 , 33 ]. The profound psychosocial implications identified in the reports—feelings of embarrassment, social withdrawal, and low self-esteem—parallel the findings of Esmann and Jemec [ 32 ], highlighting the link between HS and psychological distress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The significant impact of HS on patients’ quality of life, as reflected in our analysis, aligns with previous research underscoring the considerable burden of this condition [ 28 , 33 ]. The profound psychosocial implications identified in the reports—feelings of embarrassment, social withdrawal, and low self-esteem—parallel the findings of Esmann and Jemec [ 32 ], highlighting the link between HS and psychological distress.…”
Section: Discussionsupporting
confidence: 90%
“…HS symptomatology, as shown in our analysis, is multifaceted, reinforcing the complexity and heterogeneity of the disease [ 28 ]. The frequent occurrence of abscesses and nodules resonates with classical clinical descriptions of HS [ 29 ].…”
Section: Discussionmentioning
confidence: 92%
“…Disease severity was assessed by the clinician with the following three measures: Hurley staging, Hidradenitis Suppurativa-Physician's Global Assessment (HS-PGA) of disease, and Modi ed Sartorius Score (MSS) [12]. Patients were also asked to rate their a) HS disease severity using a scale from 0 to 10, where 0 indicated clear disease and 10 represented very severe disease [13], b) HS-related pain intensity on a scale from 0 to 10, where 0 indicated no pain at all and 10 pain as bad as it could be [14][15][16], and c) HS-related pruritus severity using a scale from 0 to 10, where 0 indicated no pruritus and 10 represented very severe pruritus because of HS lesions [16]. All participants completed seven paper-based questionnaires regarding Cutaneous Body Image (CBI), Body Image (BI), and quality of life (QoL).…”
Section: Methodsmentioning
confidence: 99%
“…It is composed of 16 items grouped under three subscales: symptoms (questions: 1-4), emotions (questions: 5-11), and functioning (questions: [12][13][14][15][16]). Subscale scores are converted to a linear scale of 0-100, where higher scores indicate more impaired levels of HRQoL.…”
Section: Skindex-16mentioning
confidence: 99%
“…With an average diagnostic delay of 10 years, and with the majority of HS patients having seen five physicians for their symptoms prior to a diagnosis, we would contend that HS awareness has high educational value in itself for both the general population as well as health professionals [3]. Patients may be very knowledgeable regarding HS, and studies have even demonstrated substantial agreement between physician and patient’s severity assessments using Hurley stage classification [4]. Even more importantly, content from patients can provide insights into the lived experience of persons suffering from HS.…”
mentioning
confidence: 99%